Factores de riesgo que influyen en el bajo peso del neonato en el Hospital General Isidro Ayora - Ruiz Reyes, Marco Stalin (2014)
Descriptive, prospective, qualitative and quantitative, cross sectional meet in order to study the risk factors that influence low birth weight, the general objective is planting determine the factors that influence the low weight of the infant in the "Hospital was conducted Isidro Ayora Loja "during the period from March to August 2013; and specific objectives were: 1) To establish the factors influencing low birth weight infant, 2) Determine the weight of newborns according to gestational age, 3) identify the etiologic agents in underweight newborn, 4) determine the maternal age influences the LBW 5) Structuring an educational proposal, aimed at mothers in gestational state of our study area. The sample consisted of 56 patients according to the inclusion and exclusion criteria. The information obtained through the medical history of each patient by collecting data sheet out previously, which was analyzed by a statistical model presenting the results in statistical tables. From the results it was found that of the 56 mothers of newborns studied the risk factor most often produces low birth weight are maternal infections with 32.14%, followed by the RPM corresponding to 21.42 %, and 16.07% preeclampsia. Of the patients studied preterm and term for weight having a greater percentage is 2000-2500 grams with 41.07% and 26.78% respectively. According to the maternal age 46.42% are between 20-35 years old and 35.7% were among children under 20 years. Also was identified that the most common cause for low birth weight being the most frequently infections with 53.57% and reduction of blood flow with 46.42%. Keywords: low birth weight LBW